Gene analysis reveals that leaf litter from Epichloë endophyte-infected perennial ryegrass alters diversity and abundance of soil microbes involved in nitrification and denitrification. (March 2021) - Chen, Zhenjiang; Jin, Yuanyuan; Yao, Xiang; Wei, Xuekai; Li, Xiuzhang; Li, Chunjie; White, James F.; Nan, Zhibiao
Abstract: Although Epichloë endophytes are present only in aboveground tissues of grasses they indirectly influence soil biological characteristics through increased litter incorporation and root exudation. Epichloë endophytes have been reported to affect the decomposition rates of litter by altering litter quality and microbial decomposers to affect soil characteristics. However, it is not well-studied that underlying effects on functional genes involved in nitrification and denitrification after incorporation of litter containing Epichloë endophytes into soil. We collected soil samples at S0 (first litter incorporation), S1 (second litter incorporation), S2 (third litter incorporation) and S3 (120 days after the third litter incorporation) times after incorporation of litter that was either infected with the fungal endophyte Epichloë festucae var. Lolii or free of Epichloë endophyte, respectively. . We sampled the soil fororganic carbon (OC), total nitrogen (TN), total phosphorus (TP), ammonium nitrogen (NH4 + -N: AN), nitrate nitrogen (NO3 − -N: NN), soil microbial biomass carbon (MBC), nitrogen (MBN), ammonia-oxidizing bacteria (AOB- amoA ) and ammonia-oxidizing archaea (AOA- amoA ) functional genes for nitrification, nitrite reduction ( nirS and nirK ) and nitrous oxide reduction ( nosZ ) functional genes for denitrification. We found that Epichloë -infected plant increased the soil properties (OC, TN, AN, NN) and microbial biomass C in S1 to S3 times, and microbial biomass N in S2 and S3 times, but reduced soil pH in S1 times and the C_N ratio in S2 and S3 times by litter incorporation. The absolute abundance of the AOB- amoA functional gene at S1 and S3 times and relative abundances of Planctomycetes, Methylobacterium, Nitosomonas, Gemmata, Geodermatophilus and Sinorhizobium in the nirK functional gene community were significantly higher in soil with Epichloë -infected litter compared to soil with Epichloë -free litter at S1 and S3 times. While the absolute abundance at S1 and S3 times and diversity at S3 times of the nirK functional gene, and the absolute abundance at S1 to S3 times and diversity at S1 times of the nosZ functional gene, and relative abundance of Proteobacteria in the AOB- amoA functional gene were significantly lower in soil with litter containing Epichloë endophyte than that of soil with litter without the endophyte. The soil moisture, and the contents of TP, OC, AN and MBN were the best explanatory variables for the altered microbial community. Our results provide a new understanding of the responses of soil nitrification and denitrification genes through incorporation of litter containing Epichloë endophytes into soil. Highlights: Soil microbial habitat environment was changed by litter incorporation. We observed an increase in the absolute abundance of AOB- amoA in EI compared to EF soil. The composition of nirK functional gene communities differed in EI and EF soil. Endophyte reduced the diversity of nosZ functional gene following litter incorporation. Soil properties were explained best the difference in functional genes.